Self efficacy dalam penggunaan kondom pada Lelaki Seks Lelaki (LSL) dengan HIV/AIDS: Literature review - Nirwanto K Rahim; Sri Yona; Agung Waluyo (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Self-efficacy for condom use related sexual risk behavior among men who have sex with men and HIV/AIDS: A literature reviewBackground: The prevalence of HIV / AIDS in the world is increasing. Men who have sex with men (MSM) is the population most vulnerable to HIV / AIDS. Transmission occurred because of the low use of condoms. Self-efficacy is the ability to belief of self against individual coping in specific situations that affect thinking, behavior, and emotional patterns that can affect attitudes in controlling motivation, behavior, social and the surrounding environmentPurpose: A literature study was explore self-efficacy in using condom and measurement of self-efficacy in condom useMethod: Literature studies used the online database Proquest, CINAHL, the literature was limited by criteria: in 2016-2019, full text and English language, with the keywords: